2013
DOI: 10.1111/ijsa.12035
|View full text |Cite
|
Sign up to set email alerts
|

Can the LTSI Predict Transfer Performance? Testing intent to transfer as a proximal transfer of training outcome

Abstract: Law enforcement personnel (n = 235) were administered the Learning Transfer Systems Inventory (LTSI) and a transfer measure after completing leadership development training. Although most studies using the LTSI have focused on validation efforts in different linguistic settings, this study is one of the few to examine the relationship between the LTSI factors and a proximal transfer outcome score (as measured by intent to transfer). Motivation to transfer, transfer design, and transfer performance expectations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 85 publications
3
55
0
4
Order By: Relevance
“…This would be especially important for future studies that include training transfer as an outcome variable because training transfer is a more objective variable compared to the LTSI factors, and participants tend to overestimate their training outcomes (e.g., Taylor, Russ‐Eft, & Chan, ). However, we regard self‐reports as the adequate method to assess the LTSI factors because the questionnaire was developed “to measure individual perceptions of transfer system constructs” (Hutchins et al, , p. 259). Persons other than the trainees themselves cannot describe these individual perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…This would be especially important for future studies that include training transfer as an outcome variable because training transfer is a more objective variable compared to the LTSI factors, and participants tend to overestimate their training outcomes (e.g., Taylor, Russ‐Eft, & Chan, ). However, we regard self‐reports as the adequate method to assess the LTSI factors because the questionnaire was developed “to measure individual perceptions of transfer system constructs” (Hutchins et al, , p. 259). Persons other than the trainees themselves cannot describe these individual perceptions.…”
Section: Discussionmentioning
confidence: 99%
“…These models focused on transfer determinants; but to test the models' adequacy, research reported that their explanatory power is moderately low (Blume et al, 2010). Recent studies (Hutchins et al, 2013;Weisweiler et al, 2013;Young, 2013) Transfer, which is focused only on motivational variables that affect trainees' transfer process. Still, although an attempt was made in grounding the model in theories reflecting motivational and emotional dynamics, more variables exist that would warrant inclusion, such as goal orientations (Gegenfurtner & Hagenauer, 2013;Laine & Gegenfurtner, 2013) or motivation to learn (Chiaburu & Marinova, 2005;Gegenfurtner, 2011b ).…”
Section: Discussionmentioning
confidence: 99%
“…Selon la théorie du comportement planifié [10] , l'intention est l'antécédent immédiat du comportement, ce qui en fait un bon prédicteur de ce dernier, laissant présager, comme suggéré par Hutchins et al [12] , la possible utilisation de la mesure de l'intention de transférer comme mesure du transfert. L'hypothèse 4 est ainsi formulée : l'intention de transférer prédit le transfert.…”
Section: Question Et Hypothèses De Rechercheunclassified
“…Les échelles « attitude envers le transfert », « perception des normes par rapport au transfert », « contrôlabilité perçue par rapport au transfert » et « SEP par rapport au transfert » ont ainsi été construites en suivant les consignes de Francis et al [14] et en s'inspirant des items de l'échelle utilisée par Shoham [15] pour la contrôlabilité perçue, et de celles utilisées par Shoham [15] et Devos et al [8] pour le SEP. L'échelle « orientation de la formation vers le transfert » (transfer design) est issue du Learning Transfer System Inventory (LTSI) traduite en français par Devos et al [8] . L'échelle « intention de transférer » est inspirée de celle de Hutchins et al [12] Le questionnaire a été pré-testé dans deux versions successives par respectivement quatre et six médecins généralistes, et approuvé par des personnes-ressources dans le cadre du transfert des acquis ou de la formation continue des médecins généralistes.…”
Section: Mesuresunclassified
See 1 more Smart Citation